Stimulating Tourist Inspiration by Tourist Experience: The Moderating Role of Destination Familiarity - Xue, Jianping; Zhou, Zhimin; Majeed, Salman; Chen, Ruixia; Zhou, Nan (Frontiers in Psychology, 2022)
The tourist experience is a core indicator of destination management for the comprehensive evaluation of destination value. Tourist experience and tourist inspiration are important concepts in the stream of research on destination marketing and management. However, these relationships remained under-explored in the extant literature. This study examined the impact of tourist experience on tourist inspiration under the moderating impact of destination familiarity. To achieve the objective of this study, data were collected online from 622 Chinese tourists. We employed partial least squares structural equation modeling (PLS-SEM) to statistically analyze the gathered data. Findings show that four types of tourist experiences, namely education, esthetics, entertainment, and escapism, significantly and positively influenced the inspired-by state of tourist inspiration, which further influenced the inspired-to-state of tourist inspiration. Destination familiarity exerted a significantly negative moderating impact on the relationship between education experience and inspired-by state of tourist inspiration. Sensitivity analysis presents that education experience was the strongest predictor of the inspired-by state followed by aesthetics, escapism, and entertainment facets of the tourist experience. Findings contribute to the theory and practice of tourism management with a robust interpretation of tourist experience, tourist inspiration, and destination familiarity to solidify the effective management of tourist destinations. Limitations and future research directions are noted.